Development of a rainwater harvesting system - Idris, Muhammad Ihsan Muhammad Ihsan Syafiqin (2024)
The demand for sustainable water management solutions has prompted the development of a portable rainwater harvesting tank system equipped with its own filtration mechanism suitable for residential und and transportability. Thus, this project proposed the development and design of a portable rainwater harvesting system that includes the filtering system, water storage and efficient piping infrastructure. The primary objectives are to design a portable water tank adaptable to various settings and fabricate a cost-effective rainwater harvesting system. The fabrication method employs innovative techniques to construct the tank and integrate a low- maintenance filtration system. The expected result is a flexible rainwater collection tank system designed to tackle water shortage challenges while providing convenience and cost-effectiveness for household use